Por la liberación y la defensa de la patria volvemos a los campos… (FEP (Federación de Estudiantes Panameños), 1976)
Letters 'ABC' filled with colour-tinted photographs of demonstrations, the Panama revolutionary front and official army Poster calling for volunteers to a public instruction campaign of the FEP, Summer 1976 PO-1469